2009
DOI: 10.4028/www.scientific.net/amr.79-82.2063
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Response and Mechanical Behavior of Plasticized PVC Actuators

Abstract: [Abstract] By changing gel and electrode shape, many different actuators could be invented. In the previous papers, we have reported that Maxwell stress generated in the PVC gels was expected as the results of polarization response of charges, and it mainly took place between the gel and the anode due to the accumulated negative charges on surface of the PVC gel near anode. Due to the existence of the Maxwell force, the PVC gel will be deformed asymmetrically and resulted in creep deformation along the anode. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…A phenomenon that an accumulation of negative charges on the gel surface near the anode was confirmed by space-charge measurement [21]. It was also found that PVC gels were separated to two layers obviously after applied an electrical field, of which the layer near the anode was thinner and softer than other layer due to the transfer of plasticizer to the anode [22]. Therefore, we believe that when an electric field is turned on, electrons are injected from the cathode into the gel, and migrate toward the anode.…”
Section: Deformation Mechanism Of Pvc Gelsmentioning
confidence: 67%
“…A phenomenon that an accumulation of negative charges on the gel surface near the anode was confirmed by space-charge measurement [21]. It was also found that PVC gels were separated to two layers obviously after applied an electrical field, of which the layer near the anode was thinner and softer than other layer due to the transfer of plasticizer to the anode [22]. Therefore, we believe that when an electric field is turned on, electrons are injected from the cathode into the gel, and migrate toward the anode.…”
Section: Deformation Mechanism Of Pvc Gelsmentioning
confidence: 67%
“…This will reduce the molecular crystallinity and the film becomes more uniform and softer. When DBA is added, the polymer network swells and forms a gel structure with polymer‐rich and polymer‐poor phases, as shown in Figure (c). The area with minute particles is the polymer‐rich phase, and the area with linear structures is the polymer‐poor phase.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, plasticisers have been used to make PVC soft and flexible since the 1920s [28], and the normal manufacturing method for plasticised PVC requires no solvent: a dispersion of plasticiser and PVC particles is simply cured at 190-200 °C [29]. The pervasiveness of the solventbased method for manufacturing PVC gel actuators may stem from the fact that the anodophilic PVC gel has almost always been manufactured using DBA plasticiser [7, [20][21][22]24,26,[30][31][32], whose flash point is 113 °C [33], whereas rigid PVC melts at about 170-180°C [34]. This has prevented heat-based manufacture and necessitated the use of solvents.…”
Section: Methodsmentioning
confidence: 99%